Endovascular Thrombectomy for Ischemic Stroke Increases Disability-Free Survival, Quality of Life, and Life Expectancy and Reduces Cost - Campbell, Bruce C. V.; Mitchell, Peter J.; Churilov, Leonid; Keshtkaran, Mahsa; Hong, Keun-Sik; Kleinig, Timothy J.; Dewey, Helen M.; Yassi, Nawaf; Yan, Bernard; Dowling, Richard J.; Parsons, Mark W.; Wu, Teddy Y.; et al. (Frontiers in Neurology, 2017)
Background: Endovascular thrombectomy improves functional outcome in large vessel occlusion ischemic stroke. We examined disability, quality of life, survival and acute care costs in the EXTEND-IA trial which used CT-perfusion imaging selection. Methods: Large vessel ischemic stroke patients with favorable CT-perfusion were randomized to endovascular thrombectomy after alteplase versus alteplase-only. Clinical outcome was prospectively measured using 90-day modified Rankin Scale (mRS). Individual patient expected survival and net difference in Disability/Quality-adjusted life years (DALY/QALY) up to 15 years from stroke were modeled using age, sex, 90-day mRS, and utility scores. Level of care within the first 90 days was prospectively measured and used to estimate procedure and inpatient care costs (US reference year 2014). Results: There were 70 patients, 35 in each arm, mean age 69, median NIHSS 15 [IQR 12-19]. The median[IQR] disability-weighted utility score at 90-days was 0.65[0.00-0.91] in the alteplase-only versus 0.91[0.65-1.00] in the endovascular group (p=0.005). Modelled life expectancy was greater in the endovascular versus alteplase-only group (median 15.6 versus 11.2 years, p=0.02). The endovascular thrombectomy group had fewer simulated DALYs lost over 15 years (median[IQR] 5.5[3.2-8.7] versus 8.9[4.7-13.8], p=0.02) and more QALY gained (median[IQR] 9.3[4.2-13.1] versus 4.9[0.3-8.5], p=0.03). Endovascular patients spent less time in hospital (median[IQR] 5[3-11] days versus 8[5-14] days, p=0.04) and rehabilitation (median[IQR] 0[0-28] versus 27[0-65] days, p=0.03). The estimated inpatient costs in the first 90-days were less in the thrombectomy group (average US15,689 versus US30,569, p=0.008) offsetting the costs of inter-hospital transport and the thrombectomy procedure (average US10,515). The average saving per patient treated with thrombectomy was US4,365. Conclusions: Thrombectomy patients with large vessel occlusion and salvageable tissue on CT-perfusion had reduced length of stay and overall costs to 90-days. There was evidence of clinically relevant improvement in long-term survival and quality of life.